1985
DOI: 10.1136/oem.42.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Coexposure to toluene and p-xylene in man: uptake and elimination.

Abstract: Eight male subjects were experimentally exposed to toluene, p-xylene, and a combination of toluene and p-xylene in order to study the influence of coexposure and exposure to different levels of each solvent on their uptake and elimination. The exposures were performed for four hours at exposure levels equivalent to or lower than the Swedish threshold limit value for toluene, 300 mg/m3 (3.2 mmollm3). During and after the exposure, solvent concentrations were measured in blood and in expired air. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
1
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
3
10
1
2
Order By: Relevance
“…However, toluene AFs from other studies were either much higher or much lower than the values reported here [41,42,45]. For C8-aromatics, while the mean respiratory AFs in many studies [29,46,49,50,[52][53][54] were lower than the 66.9% recorded in this study, other studies have reported much higher AFs [41,51]. Our results also indicated that the respiratory AFs of BTEX were much lower than 90%, which has been assumed to be the AF for toxic VOCs when assessing the human health risks of HAP exposure in many previous studies [6,[21][22][23][24]69].…”
Section: Preliminary Tests Of Real-time Afscontrasting
confidence: 51%
See 1 more Smart Citation
“…However, toluene AFs from other studies were either much higher or much lower than the values reported here [41,42,45]. For C8-aromatics, while the mean respiratory AFs in many studies [29,46,49,50,[52][53][54] were lower than the 66.9% recorded in this study, other studies have reported much higher AFs [41,51]. Our results also indicated that the respiratory AFs of BTEX were much lower than 90%, which has been assumed to be the AF for toxic VOCs when assessing the human health risks of HAP exposure in many previous studies [6,[21][22][23][24]69].…”
Section: Preliminary Tests Of Real-time Afscontrasting
confidence: 51%
“…However, compared with the mean respiratory AF in this study, Nomiyama and Nomiyama [37] reported significantly lower AFs (30%), while Yu and Weisel [40] reported much higher AFs (64%). For toluene, the results from this study were almost the same as the mean respiratory AFs of 55% and 54% reported by Wallen et al [44] and Wallen et al [46]. The mean respiratory AFs reported by Carlsson [43], Lof et al [47], and Lof et al [48] were all close to 50%, only slightly lower than the 55.9% recorded in this study.…”
Section: Preliminary Tests Of Real-time Afssupporting
confidence: 47%
“…O tolueno e o xileno são, atualmente, dois dos hidrocarbonetos aromáticos mais utilizados no meio ocupacional (Wallen et al, 1995).…”
Section: Introdução Introdução Introdução Introdução Introduçãounclassified
“…
Determinação simultânea dos ácidos hipúrico e metil-hipúrico urinários Determinação simultânea dos ácidos hipúrico e metil-hipúrico urinários Determinação simultânea dos ácidos hipúrico e metil-hipúrico urinários Determinação simultânea dos ácidos hipúrico e metil-hipúrico urinários Determinação simultânea dos ácidos hipúrico e metil-hipúrico urinários por métodos cromatográficos: comparação entre cromatografia líquida de por métodos cromatográficos: comparação entre cromatografia líquida de por métodos cromatográficos: comparação entre cromatografia líquida de por métodos cromatográficos: comparação entre cromatografia líquida de por métodos cromatográficos: comparação entre cromatografia líquida de alta eficiência e cromatografia gasosa capilar alta eficiência e cromatografia gasosa capilar alta eficiência e cromatografia gasosa capilar alta eficiência e cromatografia gasosa capilar alta eficiência e cromatografia gasosa capilar Zelaine Lima Silva, Josianne Nicácio Silveira, Márcio Jacinto, Leiliane Coelho André Amorim, Zelaine Lima Silva, Josianne Nicácio Silveira, Márcio Jacinto, Leiliane Coelho André Amorim, Zelaine Lima Silva, Josianne Nicácio Silveira, Márcio Jacinto, Leiliane Coelho André Amorim, Zelaine Lima Silva, Josianne Nicácio Silveira, Márcio Jacinto, Leiliane Coelho André Amorim, Zelaine Lima Silva, Josianne Nicácio Silveira, Márcio Jacinto, Leiliane Coelho André Amorim, Edna Maria Alvarez-Leite* Edna Maria Alvarez-Leite* Edna Maria Alvarez-Leite* Edna Maria Alvarez-Leite* Edna Maria Alvarez-Leite*
INTRODUÇÃO INTRODUÇÃO INTRODUÇÃO INTRODUÇÃO INTRODUÇÃOO tolueno e o xileno são, atualmente, dois dos hidrocarbonetos aromáticos mais utilizados no meio ocupacional (Wallen et al, 1995).Estudos têm demostrado que a exposição conjunta a estes dois solventes pode resultar no aparecimento de interações toxicocinéticas importantes, uma vez que ambos são inibidores mútuos da biotransformação. Esta inibição poderá resultar em alterações nas concentrações urinárias dos metabólitos ácido hipúrico e metil hipúrico utilizados, respectivamente, como indicadores biológicos na exposição ocupacional ao tolueno e xileno (Alessio, 1996;Plaa et al, 1992).

Assim, a utilização de métodos analíticos que permitam a identificação conjunta destes biomarcadores é de grande importância para a melhor interpretação dos resultados da monitorização biológica da exposição.

A cromatografia líquida de alta eficiência (CLAE) e a cromatografia em fase gasosa (CG) são, atualmente, os métodos mais utilizados para a determinação urinária destes metabólitos (Kira, 1977;Poggi et al, 1982;Lundberg, Sollenberg, 1986;Ogata, Taguchi, 1988;Sakai et al, 1989; Carvalho, 1991; Inoue et al, 1991;Ukai et al, 1994;Ikeda, 1995;Kawamoto et al, 1995;Amorim, Alvarez Leite, 1997;Burini, 1998).

…”
unclassified
“…The toxicokinetics of industrially used organic solvents in man have been focused upon in severallaboratory exposure experiment s (2,3,4,7,20,26,34,37,38,40,41). However, most of these stud ies were carried out with young health y volunteers with no history of occupational exposure to solvents or other agents that could affect the kinetics of the solvent studied.…”
mentioning
confidence: 99%